1981
DOI: 10.3181/00379727-166-41017
|View full text |Cite
|
Sign up to set email alerts
|

Altered Ovarian Regulation of Wound Healing during Aging

Abstract: The healing rate of full-thickness skin lesions is slower in senescent female rats (22-23 months) than in their young adult (5-6 months) counterparts. Fifty percent wound closure times were 9.46 ? 0.31 and 6.45 * 0.40 days, respectively (P < 0.001). Ovariectomy significantly slows the healing process in the mature group but not in the senescent animals. Treatment of ovariectomized rats with low-dose estradiol (0.3 pglkg body wt) restores the healing rate to nearly normal in mature rats and accelerates the heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…According to the studies, there exist a strong correlation between the systemic hormone levels and wound healing. It has been reported that the women at the post-menopausal stage taking systemic hormone replacement therapy heal wounds more effectively than the control ones [5].…”
Section: Q2mentioning
confidence: 99%
“…According to the studies, there exist a strong correlation between the systemic hormone levels and wound healing. It has been reported that the women at the post-menopausal stage taking systemic hormone replacement therapy heal wounds more effectively than the control ones [5].…”
Section: Q2mentioning
confidence: 99%
“…This has been confirmed in clinical studies (9)(10)(11) and in experimental investigations on mice and rats (12-16, t, §). Wound healing rate has even been used as a biological marker ofage in mice.T Previous results suggested that altered estrogen or androgen levels or altered sensitivity to these steroids could account, at least partially, for the slower wound repair in old rats (16). The macrophage has been reported to be an estrogenresponsive cell type.…”
mentioning
confidence: 99%
“…This has been confirmed in clinical studies (9-11) and in experimental investigations on mice and rats (12-16, t, §). Wound healing rate has even been used as a biological marker ofage in mice.T Previous results suggested that altered estrogen or androgen levels or altered sensitivity to these steroids could account, at least partially, for the slower wound repair in old rats (16 clipped and shaved on the back. Four cutaneous wounds were made on each animal by lifting the shaved skin perpendicularly to the length of the mouse and punching twice (once anteriorly on the right side and once posteriorly on the left side) with a leather punch (circumference, 4.7 mm), resulting in two wounds on each side.…”
mentioning
confidence: 99%
“…8 Furthermore, systemic hormone levels profoundly influence wound healing: post-menopausal females taking systemic hormone replacement therapy heal standardized acute wounds more rapidly than agematched controls, 9 which is in agreement with previous animal studies. 10 The presence of the estrogen receptor in normal skin fibroblasts, as well as in wound fibroblasts and inflammatory cells of both young and aged males and females (Ashcroft G, unpublished observation) suggests that local estrogen levels may influence cutaneous physiology, including the wound healing process. Moreover, it is well-documented that sex hormones modulate immune responses, and an increase in the inflammatory response in specific diseases such as gingivitis can be related to reduced estrogen levels.…”
mentioning
confidence: 99%